Evidence of Alternative Splicing as a Regulatory Mechanism for Kissr2 in Pejerrey Fish - Mechaly, Alejandro S.; Tovar Bohórquez, M. Oswaldo; Mechaly, Ariel E.; Suku, Eda; Pérez, María Rita; Giorgetti, Alejandro; Ortí, Guillermo; Viñas, Jordi; Somoza, Gustavo M. (Frontiers in Endocrinology, 2018)
Kisspeptin receptors are G-Protein-Coupled Receptors that regulate GnRH synthesis and release in vertebrates. Here, we report the gene structure of two kisspeptin receptors (kissr2 and kissr3) in pejerrey fish. Genomic analysis exposed a gene structure with 5 exons and 4 introns for kissr2 and 6 exons and 5 introns for kissr3. Two alternative variants for both genes, named kissr2_v1 and _v2, and kissr3_v1 and v2, were revealed by gene expression analyses of several tissues. For both receptors, these variants were originated by alternative splicing retaining intron 3 and intron 4 for kissr2_v2 and kissr3_v2, respectively. In the case of kissr2, the intron retention introduced two stop codons leading to a putatively truncated protein whereas for kissr3, the intron retention produced a reading shift leading to a stop codon in exon 5. Modeling and structural analysis of Kissr2 and Kissr3 spliced variants revealed that truncation of the proteins may lead to non-functional proteins, as the structural elements missing are critical for receptor function. To understand the functional significance of splicing variants, the expression pattern for kissr2 was characterized on fish subjected to different diets. Fasting induced an up-regulation of kissr2_v1 in the hypothalamus, a brain region implicated in control of reproduction and food intake, with no expression of kissr2_v2. On the other hand, fasting did not elicit differential expression in testes and habenula. These results suggest that alternative splicing may play a role in regulating Kissr2 function in pejerrey.